Plurais (in)visibilidades: representações republicanas sobre o negro (jornal A Federação - RS, 1884 – 1903) - Dihl, Tuane Ludwig (Universidade do Vale do Rio dos Sinos, 2017)
This research analyze the representations shown on porto-alegrense newspaper ‘A Federação’ – part of Rio-Grandense Republican Party (PRR) – about black people on post-abolition period, specifically between latest 19th century decades and initial years from 20st century. From editions on this newspaper, it is investigated how and the meanings given to ethnicity and color when used to give visibility to african-brazilians. Those aspects could be identified on discussions that pointed to the abolitinist and black political protagonism, on projects for the work regimes transformation ando n representantions about non-white behaviors on public spaces. It was noticed an abscense of single speeches about distinguished aspects of ‘A Federação’ editors, which reflected on equally variable representations, that could condemn or praise black people, include or exclude them from its republican project or yet tend to either give visibility or invsibility.
Keywords: A federação; Partido republicano Rio-grandense; Representações; Negros; Invisibilidade; Rio-Grandense republican party; Representations; Black people; Invisibility; ACCNPQ::Ciências Humanas::História